Development of professional competencies in engineering education - Cajander, A.; Daniels, M.; Von Konsky, Brian (Frontiers in Education, 2011)
This paper reports on a study conducted at a Swedish university in which engineering students reflect on their attainment of professional competencies using generic graduate attributes as a guiding framework. In this study, the nine graduate attributes from Curtin University in Perth, Australia were used as this framework. The Swedish students were asked to reflect on their understanding of the competencies, and to select three on which to focus over the course of the semester. Students predominantly selected professional skills, thinking skills, information skills, communication skills, and intercultural understanding. In a subsequent reflection, students were asked to self-assess improvement of their chosen attributes. Results showed that while the teaching staff judged that the students had further developed the competencies, students lacked a framework to see this for themselves and reported difficulty in reflecting on progress in professional competency attainment. This suggests that a more holistic approach should be taken earlier in the degree to focus student attention on professional competencies, and provide ongoing experience reflecting on progressive achievement.